Phishing Threats in the Age of Social Media: A User-Centric Approach - BADESCU, Ruxandra (Informatica economica, 2024)
Even today, phishing attacks continue to have a high success rate, using impersonation to trick users into revealing sensitive information. Despite the fact that the number of technology users is growing rapidly, this does not seem to provide individuals with sufficient knowledge and experience to understand cybersecurity concepts. In addition to this, not only technological shortcomings are exploited, but also human characteristics, weaknesses, that make users vulnerable when faced with potential threats. This study aims to provide an overview of phishing attacks and the rapid development of detection techniques and phishing tools in a context where cybersecurity education or training is not compulsory. The article manifests the importance of education, regardless of the technological changes that influence the daily lives of countless individuals. The present research was conducted using a literature analysis and a survey.